Former Yugoslav Republic of Macedonia : Selected Issues for the 2009 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Selected Issues paper assesses the desired level of foreign exchange reserves in the Former Yugoslav Republic of Macedonia, given its commitment to maintain the exchange rate peg. A variety of methods including popular rules of thumb, comparisons with other emerging countries, and model-based estimates suggest a target range of Euro 1.5-2 billion for reserves. The paper also looks at reserve levels that would be implied by popular rules of thumb and at benchmarks suggested by other emerging market countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet